The identification of circular extrachromosomal DNA in the nuclear genome of Trypanosoma brucei - Alsford, N.S.; Navarro, M.; Jamnadass, Ramni H.; Dunbar, H.; Ackroyd, M.; Murphy, N.B.; Gull, K.; Ersfeld, K. (Wiley, 2002)
Nuclear extrachromosomal DNA elements have been identified in several kinetoplastids such as Leishmania and Trypanosoma cruzi, but never in Trypanosoma brucei. They can occur naturally or arise spontaneously as the result of sublethal drug exposure of parasites. In most cases, they are represented as circular elements and are mitotically unstable. In this study we describe the presence of circular DNA in the nucleus of Trypanosoma brucei. This novel type of DNA was termed NR-element (NlaIII repeat element). In contrast to drug-induced episomes in other kinetoplastids, the T. brucei extrachromosomal NR-element is not generated by drug selection. Furthermore, the element is stable during mitosis over many generations. Restriction analysis of tagged NR-element DNA, unusual migration patterns during pulsed field gel electrophoresis (PFGE) and CsCl/ethidium bromide equilibrium centrifugation demonstrates that the NR-element represents circular DNA. Whereas it has been found in all field isolates of the parasites we analysed, it is not detectable in some laboratory strains notably the genome reference strain 927. The DNA sequence of this element is related to a 29 bp repeat present in the subtelomeric region of VSG-bearing chromosomes of T. brucei. It has been suggested that this subtelomeric region is part of a transition zone on chromosomes separating the relatively stable telomeric repeats from the recombinationaly active region downstream of VSG genes. Therefore, we discuss a functional connection between the occurrence of this circular DNA and subtelomeric recombination events in T. brucei.